From CAD to microfluidic chip within one day: rapid prototyping of lab-on-chip cartridges using generic polymer parts. (31st August 2020) - Podbiel, Daniel; Boecking, Lorenz; Bott, Hannah; Kassel, Julian; Czurratis, Daniel; Laermer, Franz; Zengerle, Roland; Hoffmann, Jochen
Abstract: We report on a novel rapid prototyping approach for the manufacturing of highly individualized lab-on-chip (LoC) cartridges from generic polymer parts by laser micromachining and laser welding. The approach allows an immediate implementation of microfluidic networks, components, and functionalities into an existing LoC platform without the need for an expensive and time-consuming fabrication of production tools like molds or masks. We comprehensively describe the individual process steps of the rapid prototyping procedure including a wet-chemical treatment for an easy and effective surface polishing of laser micromachined polymer parts. For laying out, we introduce a generalized diagrammatic description of microfluidic functional units in order to design application-specific cartridges for molecular diagnostic workflows. We demonstrate the usability of our prototyped cartridges by performing microfluidic experiments within. Due to the use of generic polymer parts, our rapid prototyping approach combines a high degree of freedom with an intrinsic compatibility to an established and highly developed LoC system. By enabling an experimental testing within one day, the rapid prototyping procedure shortens development cycles and boosts the evolution of microfluidic networks as well as the implementation of novel microfluidic components and functionalities.